Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fnagi.2021.716594
|View full text |Cite
|
Sign up to set email alerts
|

Serum proBDNF Is Associated With Changes in the Ketone Body β-Hydroxybutyrate and Shows Superior Repeatability Over Mature BDNF: Secondary Outcomes From a Cross-Over Trial in Healthy Older Adults

Abstract: Background: β-hydroxybutyrate (BHB) can upregulate brain-derived neurotrophic factor (BDNF) in mice, but little is known about the associations between BHB and BDNF in humans. The primary aim here was to investigate whether ketosis (i.e., raised BHB levels), induced by a ketogenic supplement, influences serum levels of mature BDNF (mBDNF) and its precursor proBDNF in healthy older adults. A secondary aim was to determine the intra-individual stability (repeatability) of those biomarkers, measured as intra-clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 65 publications
2
3
0
Order By: Relevance
“…Here, it is further elucidated the role of BHB in the protection from DR, by evidencing its association with retinal BDNF levels and activity. This was in line with previous evidence reporting the induction of specific BDNF promoters by BHB in hippocampus neuron cell lines [ 12 , 13 , 14 , 26 , 27 ] and a link between serum BHB and proBDNF in healthy older adults [ 28 ]. However, our results suggested a BDNF promotion by BHB in diabetic mice retinas, which has not been previously highlighted by other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Here, it is further elucidated the role of BHB in the protection from DR, by evidencing its association with retinal BDNF levels and activity. This was in line with previous evidence reporting the induction of specific BDNF promoters by BHB in hippocampus neuron cell lines [ 12 , 13 , 14 , 26 , 27 ] and a link between serum BHB and proBDNF in healthy older adults [ 28 ]. However, our results suggested a BDNF promotion by BHB in diabetic mice retinas, which has not been previously highlighted by other studies.…”
Section: Discussionsupporting
confidence: 92%
“… 48 Our data showed that a 3-day fast, resulting in a 10-fold increase in plasma β-HB, had no impact on plasma mBDNF but induced a small but significant increase in plasma pro-BDNF. The concomitant pro-BDNF and β-HB increase is in line with recent data by Norgren et al 49 who showed that fatty acid-induced β-HB levels correlated with circulating pro-BDNF in humans. The reason for the lack of change in mBDNF in the present study is not clear.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, there does not appear to be a strong effect of chronic elevations in ketones on plasma BDNF. None of the participants in the three studies were in a cognitive deficit, which may inhibit the potential cognitive effects that may be seen in people with schizophrenia, autism and depression [ 34 , 35 , 36 ]. This lack of change across all methods of induced ketosis, requires further research on the level of ketosis needed to achieve an increase in BDNF levels for populations with and without cognitive decline.…”
Section: Discussionmentioning
confidence: 99%